Effects of all-trans retinoic acid on the in vitro maturation of camel (Camelus dromedarius) cumulus-oocyte complexes - Islam M. SAADELDIN; Ayman Abdel-Aziz SWELUM; Mona ELSAFADI; Amer MAHMOOD; Syed Hilal YAQOOB; Musaad ALFAYEZ; Abdullah N. ALOWAIMER (The Society for Reproduction and Development, 2019)
All-trans retinoic acid (RA) is a metabolite of vitamin A and has pleiotropic actions on many different biological processes, including cell growth and differentiation, and is involved in different aspects of fertility and developmental biology. In the current study, we investigated the effects of RA on camel (Camelus dromedarius) cumulus-oocyte complex in vitro maturation (IVM). IVM medium was supplemented with 0, 10, 20, and 40 µM RA. Application of 20 µM RA significantly reduced the proportion of degenerated oocytes and significantly improved oocyte meiosis and first polar body extrusion compared to the control and other experimental groups. Retinoic acid significantly reduced the mRNA transcript levels of apoptosis-related genes, including BAX and P53, and reduced the BAX/BCL2 ratio. In addition, RA significantly reduced the expression of the Transforming growth factor beta (TGFβ) pathway-related transcripts associated with the actin cytoskeleton, ACTA2 and TAGLN; however, RA increased TGFβ expression in cumulus cells. The small molecule SB-431542 inhibits the TGFβ pathway by inhibiting the activity of activin receptor-like kinases (ALK-4, ALK-5, and ALK-7); however, combined supplementation with RA during IVM compensated for the inhibitory effect of SB-431542 on cumulus expansion, oocyte meiosis I, and first polar body extrusion in activated oocytes. The current study shows the beneficial effects of RA on camel oocyte IVM and provides a model to study the multifunctional mechanisms involved in cumulus expansion and oocyte meiosis, particularly those involved in the TGFβ pathway.